Peran Teknologi Digital Dalam Mengembangkan Metode Tarbiyatul Islamiyah - Rumondang Bulan (INKLUSIF: Jurnal Pendidikan Islam, 2025)
This article discusses the role of digital technology in developing Tarbiyatul Islamiyah methods as a response to the dynamics of modern education. Using a library research approach, this study analyzes literature related to the digitalization of learning, the effectiveness of technology in delivering Islamic educational materials, and the ethical challenges that arise within Islamic pedagogy. Findings indicate that digital platforms such as videos, e-learning, Quran/Hadith applications, and social media significantly enrich the tarbiyah process by enhancing interactivity, accessibility, and personalization. Technology also strengthens instructional effectiveness through features like virtual classrooms, automated assessments, and learning analytics. However, digitalization presents challenges, including low digital literacy, the risk of misinformation in religious content, and the need for proper etiquette and ethics in the digital space. With wise and responsible utilization, digital technology has the potential to become a strategic tool in shaping an adaptive, effective, and ethically grounded Islamic educational framework. Artikel ini membahas peran teknologi digital dalam mengembangkan metode Tarbiyatul Islamiyah sebagai respons terhadap dinamika pendidikan modern. Melalui pendekatan library research, penelitian ini menganalisis literatur terkait digitalisasi pembelajaran, efektivitas teknologi dalam penyampaian materi, serta tantangan etika yang muncul dalam konteks pendidikan Islam. Hasil kajian menunjukkan bahwa penggunaan platform digital seperti video, e-learning, aplikasi Quran/Hadits, dan media sosial mampu memperkaya proses tarbiyah dengan meningkatkan interaktivitas, aksesibilitas, dan personalisasi materi. Teknologi juga mendukung penguatan efektivitas pengajaran melalui fitur kelas virtual, evaluasi otomatis, dan analitik pembelajaran. Namun, digitalisasi menghadirkan tantangan berupa rendahnya literasi digital, potensi penyalahgunaan konten agama, serta pentingnya penerapan adab dan etika dalam ruang digital. Dengan pemanfaatan yang bijak, teknologi digital berpotensi menjadi sarana strategis dalam membentuk tarbiyah yang adaptif dan berkarakter Islami.